Exploring the Potential of T-Cells for a Universal Influenza Vaccine - Sharon Vijayanand; Keegan Braz Gomes; Rikhav P. Gala; Mohammad N. Uddin; Martin J. D’Souza (Vaccines, 2020)
Among the four types of influenza viruses, the influenza A strains and their subtypes have been responsible for causing worldwide pandemics and seasonal epidemics [...]